Does drilling affect the hearing of contralateral normal ear after mastoid surgery? - Meena, Neelam; ., Purnima; Arya, Pankaj; Gupta, Shubhangi; Jat, Kailash Singh; Sharma, Man Prakash; Singhal, Pawan; Sharma, Anjani Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Chronic otitis media (COM) is a recurrent infection of the middle ear and/or mastoid air cells affecting 2-3% of global population. Mastoidectomy is the mainstay of the treatment of COM. Bone drilling during mastoidectomy procedure exposes both the ears to acoustic trauma leading to sensorineural hearing loss. The present study was conducted to assess the possible deleterious effect of drilling on hearing of contralateral normal ear by monitoring pre-operative and post-operative pure tone audibility (PTA) and otoacoustic emissions (OAE). Aims and objectives were to evaluate the effect of drill- generated noise on hearing in non-operated ear during mastoidectomy in terms of hearing loss, its nature and duration and recovery of hearing loss. Methods: An observational study was carried out in ENT department at SMS medical college and hospital, Jaipur. Total 40 patients were studied. Pre-operative and post-operative PTA and OAE were studied and compared. Mean drilling time during mastoid surgery was also studied. Results: Out of 40 subjects, maximum patients were 11-20 years of age group (37.5%) with female preponderance (57.5%). All had undergone mastiodectomy. Only 6 (15%) subjects had transient sensorineural hearing loss of contralateral normal ear as determined by comparing pre-operative and post-operative PTA and OAE. The mean recovery time was 2-3 days. The study had shown significant effect of drill generated noise on hearing of contralateral healthy ear following mastoidectomy. Conclusions: Drill-generated noise can’t be lowered to a great extent therefore drilling time should be minimized during mastoid surgeries.